Trade dynamics in the East Asian miracle: A time series analysis of US-East Asia commodity trade, 1962-1992 - Terrie Carolan; Jesse Mora; Nirvikar Singh (University of California, Santa Cruz Institute for International Economics (SCIIE), 2012)
We examine the composition of bilateral trade between the United States and eight Asian Pacific economies from 1962 to 1992. Two complementary time series analyses of individual commodities at the SITC four-digit level indicate that significant changes occurred in trade composition during this period. We use a measure of normalized trade balances, developed by Gagnon and Rose (1995). For the eight bilateral trade relationships, commodities representing from fifty to seventy percent of 1992 dollar trade have shown statistically significant changes in the magnitude and, in some cases, in the direction of normalized trade balances, over the thirty-year period. Results support the conclusion that changes in trade patterns in both low-tech industries, such as textiles and clothing, and more high-tech industries, such as electronic parts and electronic goods, were important in the development of the East Asian economies.
Keywords: F02; F14; F17; O14; 330; international trade flows; time series; ADF; KPSS; trends; economic development